PENERAPAN MERDEKA BELAJAR KAMPUS MERDEKA DI FAKULTAS TARBIYAH UNIVERSITAS ISLAM ZAINUL HASAN GENGGONG - Faiz Safinatun Najah; Abdul Aziz Wahab; Muhammmad Hifdil Islam (PAI RAFAH, 2022)
The impact of Coronavirus in 2019 was very influential, especially in the world of education, the creation of the latest and most important curriculum variants initiated by the Minister of Education and Culture, Mr. Nadiem Anawar Makarim, gave the views of the young generation of Indonesia. The aim of this program is to provide students with enjoyment and seriousness in education. However, to find out whether this curriculum change is good or not, research is needed, especially in terms of students' willingness to participate in an independent campus supervised by Mr. Nadiem himself, because in my opinion, it is. Hopefully, this research can give room to the government to always evaluate the curriculum in Indonesia, especially Zainul Hasan Islamic University, Tarbiyah Faculty, which is the object of this research. The researcher uses the field research method by explaining various phenomena that occur in the field related to the positive and negative things that occur, so that it can be concluded that the implementation and readiness of students is quite good, but there needs to be more preparation. and stabilization so that the reports in it are satisfactory. The method of data collection is observation, interview, documentation and collection of information from various sources in the form of books, articles, journals and the Internet.